2006
DOI: 10.1038/sj.cdd.4401887
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-independent death of meiotic and postmeiotic cells overexpressing p53: calpain involvement

Abstract: In a model of male sterility (MTp53) owing to enforced p53 expression in spermatocytes II and spermatids of transgenic mice, we focused on the role of caspases. Most of them are expressed in all differentiation stages, but only the transcriptional levels of caspase-2 and caspase-3 are modified in MTp53 germ cells. In normal testis, cleaved caspase-3 and caspase-9 are detected during the elongation of spermatids. Despite this constitutive presence of caspases during terminal differentiation, calpains are the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…It has been reported that Fas/FasL is involved in spermatogenic cell death during development, adulthood and after toxic exposure (Mishra et al 2006). Calpain and the p53 subfamily have also been reported to be involved in male germ cell death (Coureuil et al 2006, Petre-Lazar et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Fas/FasL is involved in spermatogenic cell death during development, adulthood and after toxic exposure (Mishra et al 2006). Calpain and the p53 subfamily have also been reported to be involved in male germ cell death (Coureuil et al 2006, Petre-Lazar et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…When apoptosis in pachytene spermatocytes occurs as a result of stimuli such as heat or hormone deprivation, it appears that only the intrinsic pathway is stimulated (Sinha Hikim et al 2003). A caspaseindependent mechanism triggered by calpain activation is another mechanism that has been suggested to be involved in germ cell apoptosis (Coureuil et al 2006). Some members of the p53 family and high [Ca 2C ] i also appear to be important regulators of apoptotic death in spermatogenic cells (Mishra et al 2006, Petre-Lazar et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Primers have been previously assayed for the absence of genomic DNA amplification (Coureuil et al, 2006) and all reactions have been performed in parallel with negative controls lacking cell lysates (data not shown).…”
Section: Single-step Rt-pcrmentioning
confidence: 99%
“…Specific primers were used for caspase-2 L (F: ccaggccaaagggggcagtttcag, R: gtgtggttctttccatcttgctgg) (Coureuil et al, 2006), caspase-9 (F: catccttgtgtcctactccacc, R: cagctttttccggaggaagt), caspase-3 (F: gagcactggaatgtcatctcg, R: ttgcgtggaaagtggagtc), and ␤-actin (F: acccacactgtgcccatctac, R: cttcatggtgctaggagccag) as loading control.…”
Section: Single-step Rt-pcrmentioning
confidence: 99%
“…This complex physiological process includes chromatin reorganization, cytoplasm elimination, acrosome formation, and flagellum development in the seminiferous tubules of the testis and epididymis (O'Donnell et al 2001, Bettegowda et al of laboratory gene chips, as well as their physiological and biochemical functions (Coureuil et al 2006, Macqueen et al 2010, Hering et al 2014. CAPN1 is a calcium-regulated cysteine protease that has been described in a wide range of cellular processes, including apoptosis, migration, and cell-cycle regulation ( Santos et al 2012).…”
Section: Introductionmentioning
confidence: 99%